Polymeric Pathogen-Like Particles-Based Combination Adjuvants Elicit Potent Mucosal T Cell Immunity to Influenza A Virus - Kingstad-Bakke, Brock; Toy, Randall; Lee, Woojong; Pradhan, Pallab; Vogel, Gabriela; Marinaik, Chandranaik B.; Larsen, Autumn; Gates, Daisy; Luu, Tracy; Pandey, Bhawana; Kawaoka, Yoshihoro; Roy, Krishnendu; et al. (Frontiers in Immunology, 2021)
ABSTRACT Eliciting durable and protective T cell-mediated immunity in the respiratory mucosa remains a significant challenge. Polylactic-co-glycolic acid (PLGA)-based cationic pathogen-like particles (PLPs) loaded with TLR agonists mimic biophysical properties of microbes and hence, simulate pathogen-pattern recognition receptor interactions to safely and effectively stimulate innate immune responses. We generated micro particle PLPs loaded with TLR4 (glucopyranosyl lipid adjuvant, GLA) or TLR9 (CpG) agonists, and formulated them with and without a mucosal delivery enhancing carbomer-based nanoemulsion adjuvant (ADJ). These adjuvants delivered intranasally to mice elicited high numbers of influenza nucleoprotein (NP)-specific CD8+ and CD4+ effector and tissue-resident memory T cells (TRMs) in lungs and airways. PLPs delivering TLR4 versus TLR9 agonists drove phenotypically and functionally distinct populations of effector and memory T cells. While PLPs loaded with CpG or GLA provided immunity, combining the adjuvanticity of PLP-GLA and ADJ markedly enhanced the development of airway and lung TRMs and CD4 and CD8 T cell-dependent immunity to influenza virus. Further, balanced CD8 (Tc1/Tc17) and CD4 (Th1/Th17) recall responses were linked to effective influenza virus control. These studies provide mechanistic insights into vaccine-induced pulmonary T cell immunity and pave the way for the development of a universal influenza and SARS-CoV-2 vaccines.